2014
DOI: 10.1182/blood-2014-01-551457
|View full text |Cite
|
Sign up to set email alerts
|

Defective endomitosis during megakaryopoiesis leads to thrombocytopenia in Fanca−/− mice

Abstract: Key Points Fanca −/− megakaryocytes accumulate genomic instability through endomitotic cycles. Defective endomitosis induces senescence of Fanca−/− megakaryocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Such patients suffer from progressive bone marrow failure, pancytopenia and predisposition to cancer. 50 Knockout mouse studies revealed that FANCA is needed for normal megakaryopoiesis and platelet production. Megakaryocytes in the deficient mice were found to be in a senescent state.…”
Section: Fanca Fanccmentioning
confidence: 99%
“…Such patients suffer from progressive bone marrow failure, pancytopenia and predisposition to cancer. 50 Knockout mouse studies revealed that FANCA is needed for normal megakaryopoiesis and platelet production. Megakaryocytes in the deficient mice were found to be in a senescent state.…”
Section: Fanca Fanccmentioning
confidence: 99%
“…Importantly, persistent anaphase bridges have been observed in haematopoietic cells of FA mice, even in unperturbed conditions and are associated with cytokinesis failure and increased apoptotic cell death, 161 suggesting that endogenous replication stress or unresolved DNA damage that persists in mitosis may contribute to bone marrow failure and account for the exacerbated p53/p21 activation observed in FA 171 . Recently, the FA pathway has also been shown to counteract physiologic stress during megakaryopoiesis, preventing CFS instability and cell division abnormalities associated with defective megakaryocyte differentiation and thrombocytopenia of FA mice 282 . Finally, a variant form of xeroderma pigmentosum (XPV) is a cancer-prone disease that is caused by mutations in the gene coding for the TLS polymerase Polη, a protein shown to have a role in DNA synthesis at CFSs 6 …”
Section: The Role Of Mitotic Replication Stress In Human Diseasementioning
confidence: 99%
“…It is generally accepted that FANC pathway-deficient mice present mild hematopoietic phenotypes (49). The Fanca -/model we used (50) is known to present reduced platelet counts, which mimics patient thrombocytopenia, and altered immunoglobulin formation in association with alterations in the DNA damage response and B cell differentiation (51)(52)(53), abnormalities already reported in FA patients (54). Nevertheless, Fanca -/and WT mice, independently of their ages (3-6 months old, i.e., young, or more than 1 year old, i.e., old) present similar levels of Lin -Sca + Kit + (LSK) cells and their 3 subpopulations, longterm HSCs (LT-HSCs, Flt3 -CD34 -), short-term HSCs (ST-HSCs, Flt3 -CD34 + ), and multipotent progenitors (MPPs, Flt3 + CD34 + ), on which the maintenance of hematopoiesis depends (Figure 4, A-C).…”
Section: Fanc Core Complex Loss Of Function Leads To Mitf Overexpressmentioning
confidence: 99%